Environmental Impact of a Ground Source Heat Pump system of in a Mediterranean residential building – a Preliminary Assessment - Aresti, Lazaros; Christodoulides, Paul; Florides, Georgios A.; Skaliontas, A. (My University, 2021)
Renewable Energy Systems (RES) have gained high attention in recent years due to the constant “fight” against the use of fossil fuels. Ground Source Heat Pump (GSHP) systems (consisting of ground heat exchangers (GHEs) and HPs) exploit Geothermal Energy (a RES) and are used for space heating and cooling, exhibiting a superior performance than the conventional Air Source Heat Pump (ASHP) systems. This research focuses on the ecological aspect of GSHP systems, examining a case study in the Mediterranean island of Cyprus to determine the environmental impact of such systems when installed in high- and low-insulated residential buildings. At first, the GLD software is used to estimate the required GHEs’ parameters for the high and low building’s load. The Ecoinvent database in combination with the openLCA software is then used to perform the Life Cycle Analysis (LCA) of the system and calculate the environmental impact of both cases. The yearly heating and cooling loads of the building are used as a functional unit, with the system boundaries containing only the GHEs manufacturing and the operation of the system. An ASHP system is set as the baseline for both high and low insulations of a residential building. The GSHP system is compared to the baseline in percentage deviation. The LCA comparative results indicate that the GSHP system being a renewable energy solution, is also the most environmental-friendly solution.
Keywords: GHE; LCA; GSHP system; Environmental Impact